Endometrial receptivity array: Clinical application - Mahajan, Nalini (J Hum Reprod Sci, 2015)
Human implantation is a complex process requiring synchrony between a healthy embryo and a functionally competent or receptive endometrium. Diagnosis of endometrial receptivity (ER) has posed a challenge and so far most available tests have been subjective and lack accuracy and a predictive value. Microarray technology has allowed identification of the transcriptomic signature of the window of receptivity window of implantation (WOI). This technology has led to the development of a molecular diagnostic tool, the ER array (ERA) for diagnosis of ER. Use of this test in patients with recurrent implantation failure (RIF) has shown that the WOI is displaced in a quarter of these patients and use of a personalized embryo transfer (pET) on the day designated by ERA improves reproductive performance. Our results in the Indian population revealed an endometrial factor in 27.5% RIF patients, which was significantly greater than the non-RIF group 15% (P = 0.04). After pET, the overall ongoing pregnancy rate was 42.4% and implantation rate was 33%, which was at par with our in-vitro fertilization results over 1-year. We also performed ERA in patients with persistently thin endometrium, and it was reassuring to find that the endometrium in 75% of these patients was receptive despite being 6 mm or less. A pregnancy rate of 66.7% was achieved in this group. Though larger studies are required to validate these results ERA has become a useful tool in our diagnostic armamentarium for ER.